UPAYA MENINGKATKAN KEMAMPUAN MENGENAL LAMBANG BILANGAN ANAK USIA DINI MELALUI PERMAINAN KARTU ANGKA BERGAMBAR - Rosida Br Purba; Juli Yanti Harahap; Novita Friska; Aminda Tri Handayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to improve early childhood’s ability to recognize number symbols through picture number card games at TK Methodist El-Shadday Perbaungan. The research used Classroom Action Research (CAR) conducted in two cycles involving 13 children in group A. Data were collected through observation and documentation using observation checklists. The results showed a significant increase in children’s ability to recognize number symbols after implementing the picture number card game. The percentage of children reaching the “very good” category increased to 86.86% in the second cycle. Thus, picture number card games effectively enhance number symbol recognition skills in early childhood.